2024
DOI: 10.1039/d3sc05387c
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the competitive adsorption of hydrogen and hydroxyl intermediates on Ru by d–p orbital hybridization for hydrogen electrooxidation

Youkai Feng,
Siguang Lu,
Luhong Fu
et al.

Abstract: Strengthening the hydroxyl binding energy (OHBE) on Ru surfaces for efficient hydrogen oxidation reaction (HOR) in alkaline electrolytes at the expense of narrowing effective potential window (EPW) increases the risk...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The Cu-UPD analysis showed that the ECSA of Ru 1 W 0.14 Zn 1.47 O x reached 116 m 2 g −1 (Figure 8c). After normalization by ECSA, the specific activity (j 0,s ) of Ru 1 W 0.14 Zn 1.47 O x was found to be 0.026 mA cm ECSA −2 , close to that of the commercial Ru/C catalyst [34]. This suggests that the enhanced HOR activity of Ru 1 W 0.14 Zn 1.47 O x can be attributed to the favorable structure created, which has abundant exposed active sites.…”
Section: Electrochemical Characterizationmentioning
confidence: 51%
“…The Cu-UPD analysis showed that the ECSA of Ru 1 W 0.14 Zn 1.47 O x reached 116 m 2 g −1 (Figure 8c). After normalization by ECSA, the specific activity (j 0,s ) of Ru 1 W 0.14 Zn 1.47 O x was found to be 0.026 mA cm ECSA −2 , close to that of the commercial Ru/C catalyst [34]. This suggests that the enhanced HOR activity of Ru 1 W 0.14 Zn 1.47 O x can be attributed to the favorable structure created, which has abundant exposed active sites.…”
Section: Electrochemical Characterizationmentioning
confidence: 51%
“…[29] Meanwhile, as presented in the Ru 3p and Ti 2p core-level spectrum (Figure S7b), the Ru 3p 3/2 and Ru 3p 1/2 peaks, located respectively at 462.3 and 485.0 eV, could also be attributed to the Ru 0 for metallic Ru. [30,31] The peaks at 464.5 and 458.8 eV with the spin-orbit splitting of 5.7 eV are assigned to typical Ti 2p 1/2 and Ti 2p 3/2 in TiO 2 , respectively. [32] The O 1s spectrum (Figure S7c) includes two characteristic peaks: one peak at 530.1 eV attributed to the lattice oxygen and another broad peak at near 532 eV referred to the oxygen vacancy and surface chemisorbed oxygen.…”
Section: Resultsmentioning
confidence: 97%
“…In fact, the adsorption behaviors of H* and OH* on the active sites are competitive, and excessive OHBE will result in high coverage of hydroxyl on the catalyst surface, and this will hinder the adsorption of hydrogen during the alkaline HOR process. 76,77 To gain deeper insight into the volcanic relationship of the HOR activity with the introduction of increasing boron (Fig. S29†), calculation models with a slight proportion of the Ni–O–B interface (Ni@B s C) and a large proportion of the Ni–O–B interface (Ni@B r C) were also constructed to investigate the relationship between the alkaline HOR activity and OHBE (Fig.…”
Section: Resultsmentioning
confidence: 99%